Biological nitrogen fixation: rates, patterns and ecological controls in terrestrial ecosystems - Vitousek, Peter M. (The Royal Society, 2013)
New techniques have identified a wide range of organisms with the capacity to carry out biological nitrogen fixation (BNF)—greatly expanding our appreciation of the diversity and ubiquity of N fixers—but our understanding of the rates and controls of BNF at ecosystem and global scales has not advanced at the same pace. Nevertheless, determining rates and controls of BNF is crucial to placing anthropogenic changes to the N cycle in context, and to understanding, predicting and managing many aspects of global environmental change. Here, we estimate terrestrial BNF for a pre-industrial world by combining information on N fluxes with (15)N relative abundance data for terrestrial ecosystems. Our estimate is that pre-industrial N fixation was 58 (range of 40–100) Tg N fixed yr(−1); adding conservative assumptions for geological N reduces our best estimate to 44 Tg N yr(−1). This approach yields substantially lower estimates than most recent calculations; it suggests that the magnitude of human alternation of the N cycle is substantially larger than has been assumed.